2010
DOI: 10.1088/0031-8949/2010/t142/014015
|View full text |Cite
|
Sign up to set email alerts
|

New phenomena in variable-density Rayleigh–Taylor turbulence

Abstract: This paper presents several issues related to mixing and turbulence structure in buoyancy-driven turbulence at low to moderate Atwood numbers, A, found from direct numerical simulations in two configurations: classical Rayleigh-Taylor instability and an idealized triply periodic Rayleigh-Taylor flow. Simulations at A up to 0.5 are used to examine the turbulence characteristics and contrast them with those obtained close to the Boussinesq approximation. The data sets used represent the largest simulations to da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
64
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 29 publications
7
64
0
Order By: Relevance
“…The simulations provide much of the data needed to calibrate an engineering model and produce coefficient sets for a range of values of α. High Reynolds number DNS is now becoming feasible for the relatively simple problem considered here, see for example Livescu et al [22], and could provide very valuable confirmation of the results presented here. However, the use of three-dimensional simulation on more complex problems (e.g.…”
Section: Discussionsupporting
confidence: 74%
“…The simulations provide much of the data needed to calibrate an engineering model and produce coefficient sets for a range of values of α. High Reynolds number DNS is now becoming feasible for the relatively simple problem considered here, see for example Livescu et al [22], and could provide very valuable confirmation of the results presented here. However, the use of three-dimensional simulation on more complex problems (e.g.…”
Section: Discussionsupporting
confidence: 74%
“…Note the close agreement between this theoretical PDF curve and the PDF data calculated from the density field data. Consistent with previous studies of variable density turbulent mixing [3][4][5], the density PDFs in all test cases are skewed toward lower density values. To be more quantitative, the skewness (S) and flatness (F) are calculated for cases Se2, Be2, Pa06e2, and Ie2 according to,…”
Section: (A) (B)supporting
confidence: 88%
“…First, it was observed that buoyant flows have an asymmetric mixing rate. This manifests through a skewed density probability density function (PDF) and indicates that the more dense fluid in the RT unstable configuration mixes at a slower rate than the less dense fluid [3][4][5]. Second, as a consequence of this, the penetration depth of larger density fluids exceeds that of lower density fluids [3].…”
Section: Introductionmentioning
confidence: 99%
“…whereas the caloric equation of state is 20) where the specific heat at constant pressure for the mixture is calculated as the mass fractionweighted sum of the individual specific heats. Gases obeying equation (2.20) are usually called 'perfect'; in this case, the specific heats vary with temperature owing to energy contributions beyond those contained in translational motions.…”
Section: (C) Continuum Descriptions (I) Navier-stokes Equationsmentioning
confidence: 99%
“…HRT allows the study of turbulence and mixing without the complications owing to inhomogeneities or mixing layer edges, but retaining the basic nonlinearities and energy production mechanism as the classical RTI case. DNS results for the incompressible RTI problem are reported in references [15,25,87] with the MIRANDA code on up to 3072 3 meshes and references [20,88,89] with the CFDNS code on up to 4096 2 × 4032 meshes. All MIRANDA runs have been performed at A = 0.5, whereas CFDNS has been used for A = 0.04-0.9.…”
Section: (I) Direct Numerical Simulations Of Rayleigh-taylor Instabilmentioning
confidence: 99%